HUBUNGAN LITERASI DINI TERHADAP KEMAMPUAN MEMBACA SISWA KELAS II SDN DI GUGUS II KECAMATAN CAKRANEGARA TAHUN PELAJARAN 2019/2020 - I Made Yudiana Dharma; Siti Rohana Hariana Intiana; Hery Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2020)
This study aims to identify early literacy given by parents to kids, identify students reading abilities and identify the presence or absence of early literacy relationships with the reading ability of class II students at Cluster 02 Cakranegara Academic Year 2019/2020 and what the level of the relationship is. This type of research is correlational. The population in this study is 100 scattered from three schools. Data collection used was a questionnaire and observation method with instruments in the form of questionnaires and rubrics. The data in this study use a Likert scale with interval data types. The results of identification of early literacy and the results of students' reading ability show in the category of sufficient and good and hypothesis testing in this study used the Product Moment formula. The results of data analysis showed N = 100 at a significance of 5%, the results obtained 0.826 ()> 0.195 (), then the proposed hypothesis () was accepted. So, there is a relationship between early literacy and the ability to read in class II Cluster 02 Cakranegara Academic Year 2019/20120. Suggestions are proposed so that related parties such as parents, schools, and teachers pay more attention to pre-school literacy in order to prepare the basis of good reading skills for school-aged children.